Surfactant science and technology : retrospects and prospects - Romsted, Laurence S. (CRC Press, 2014)
"Written by the stars of surface and colloid chemistry, this edited work covers developments in the field of association colloid chemistry. The book presents an overview of the direction of the field and gives insight into the forces controlling surfactant and polymer self-assembly. The text addresses numerous research areas, including rheology, surfactant ionic liquids, foams, forces responsible for structural changes of micelles, polymeric surfactants, phase separation, surfactant interactions with solid surfaces, protein and enzymesurfactant interactions, solubilization, mesophases in concentrated solutions, enhanced oil recovery, surfactants for liquid CO2, and biobased surfactants"--